Development of a multi-tier system for the analysis of ice crystallography of Antarctic shelf ice - McEwen, Steven (Department of Civil Engineering, 2025)
This research delves into the complex ice dynamics of the under-studied Antarctic shelf ice, aiming to establish a comprehensive, multilevel approach for analyzing ice layer crystallography in these regions, with a specific focus on c-axis orientations and grain sizes. This approach encompasses the design of an analytical apparatus, methodologies for ice core collection and analysis, and the development of automation software to facilitate the analysis process. The study achieves its objectives by forming a layered reference framework for shelf ice, crafting a functional Rigsby stage for c-axis analysis, producing a reliable set of samples, and developing software for automated data interpretation. The results, demonstrated statistically and graphically, reveal a random c-axis distribution and grain sizes typical of shallow depths, thereby corroborating existing literature. The absence of a clear relationship between grain sizes and grain orientations within samples from the same core reinforces the evidence of a random distribution at these depths. While the results do not yield definitive patterns, this research makes a significant contribution by establishing a robust methodology for data analysis and visualization, thus setting the stage for future studies to probe deeper ice core samples, expand sample size and diversity, and incorporate more variables in the analysis. This study offers crucial insights into the properties of shallow-depth melt ice in the Antarctic shelf ice, thereby laying the groundwork for a more profound understanding of complex ice dynamics. Moreover, this research enriches the scientific understanding of ice shelves globally, providing a valuable foundation for addressing critical issues related to climate change. By advancing our knowledge of ice crystallography, this study informs global climate models and policy decisions, highlighting the broader implications of Antarctic ice dynamics on sea-level rise and global climate patterns